1992
DOI: 10.1104/pp.100.1.225
|View full text |Cite
|
Sign up to set email alerts
|

Maturation Proteins and Sugars in Desiccation Tolerance of Developing Soybean Seeds

Abstract: The desiccation-tolerant state in seeds is associated with high levels of certain sugars and maturation proteins. The aim of this work was to evaluate the contributions of these components to desiccation tolerance in soybean (Glycine max [L.] Merrill cv Chippewa 64). When axes of immature seeds (34 d after flowering) were excised and gradually dried (6 d), desiccation tolerance was induced. By contrast, seeds held at high relative humidity for the same period were destroyed by desiccation. Maturation proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
198
2
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(214 citation statements)
references
References 35 publications
9
198
2
3
Order By: Relevance
“…Estas proteínas, primeiramente descobertas em embriões de algodão, nomeadas proteínas lea, moduladas por ácido abscísico, acumulam em embriões de sementes de milho e cevada, durante os estádios mais tardios do desenvolvimento, em fase correspondente à aquisição de tolerância à dessecação (Bostock e Quatrano, citados por Leprince et al, 1993) e a sua expressão cessa rapidamente após a germinação (Blackman et al, 1991;Blackman et al, 1992). Segundo Thomann et al (1992) e Rosa et al (2004), proteínas lea também se acumulam em embriões de sementes de milho durante a lenta secagem, em fase correspondente à aquisição de tolerância à dessecação.…”
Section: Introductionunclassified
“…Estas proteínas, primeiramente descobertas em embriões de algodão, nomeadas proteínas lea, moduladas por ácido abscísico, acumulam em embriões de sementes de milho e cevada, durante os estádios mais tardios do desenvolvimento, em fase correspondente à aquisição de tolerância à dessecação (Bostock e Quatrano, citados por Leprince et al, 1993) e a sua expressão cessa rapidamente após a germinação (Blackman et al, 1991;Blackman et al, 1992). Segundo Thomann et al (1992) e Rosa et al (2004), proteínas lea também se acumulam em embriões de sementes de milho durante a lenta secagem, em fase correspondente à aquisição de tolerância à dessecação.…”
Section: Introductionunclassified
“…However, these proteins are not capable by themselves of promoting desiccation tolerance and, hence, maintaining seed viability [26].…”
Section: Resultsmentioning
confidence: 99%
“…The high green seed indices in the BRS 251 Robusta cultivar showed the susceptibility of the genotype, but some aspects should be considered, such as the difficulty in standardizing the development stages for the different cultivars and the smaller seed size of Robusta, that may have contributed to a premature classification of the R 6 stage and consequently greater stress effect. Several authors have reported difficulties in establishing precise identifications among the seed development stages and the irregularity of maturation among plants (Crookston and Hill, 1978;Blackman et al, 1992;Marcos Filho, 2005).…”
Section: Resultsmentioning
confidence: 99%